Model Kuantum dalam Pembelajaran Bahasa Indonesia - Vebbi Andra (Tarbawy : Jurnal Pendidikan Islam, 2017)
This research is an action research that uses descriptive methods. The technique of collecting data uses observational studies, documentation, and interviews. While data analysis is done by analyzing all available data from various sources, reducing data where data reduction is done by making abstractions, compiling data in units, namely data arranged in categorized units, categories done while making coding, carry out checks on the validity of data, interpretation of data, and conclusions. The results of the study show that the implementation of Indonesian language learning with a quantum model can be said to have succeeded. This can be seen from the results of the tests (evaluations) carried out by the teacher towards students, where the stages of learning that are carried out (starting from the pre-cycle to the first and second cycles) always experience a continuous increase in good value.